ANALISIS PENGARUH PENGETAHUAN INVESTASI, PELATIHAN PASAR MODAL, MODAL INVESTASI MINIMAL DAN PERSEPSI RISIKO TERHADAP MINAT INVESTASI MAHASISWA DI PASAR MODAL (STUDI PADA PT PHINTRACO SEKURITAS BRANCH OFFICE SEMARANG) - Theresia Tyas Listyani; Muhammad Rois; Slamet Prihati (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2019)
The purpose of research is to analyse the effects of investment knowledge, capital market training, minimum investment capital and risk perception on student investment interest in capital market (study at PT Phintraco Sekuritas Branch Office Semarang). The design of this study is a causally applied quantitative research. The data used are primary data and secondary data. Method of collecting data used questioner. The sampling technique used was purposive sampling, and the amount of the sample are 98 respondents. The test of the instruments was analysed by using validity test and realibility test. Data analysis method used is Multiple Linear Regression Analysis. The result of t test showed that investment knowledge and risk perception had no effect toward student investment interest. Capital market training and minimum investment capital had an effect toward student investment interest. Investment knowledge, capital market training, minimum investment capital and risk perception simultaneously effect the student investment interest.